Eksistensi Pasal 14 Undang-Undang Tindak Pidana Korupsi No.31 Tahun 1999 Jo Undang-Undang No. 20 Tahun 2001 Terhadap Praktek Penegakan Hukum - Dita Rosalia Arini (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2022)
The content that contained in article 14 of the Corruption Act related to law enfocement is a legal corridor that must be condered in its implementation. The issue that will be raised is how does article 14 of the Corruption Act against the Law Enforcement Practices Exist? The method used in this journal is the normative juridicial method. The results of the study indicate that the existance of the regulations containd in the provisions of article 14 is a limiter and determinant of whether other criminal acts can be tried as a criminal act of corruption, so that not all criminal acts must be resolveds by corruption trial